A bio‐inspired backbone formation protocol in cognitive radio networks. (31st July 2022) - Kumar, Santosh; Murmu, Mahendra Kumar; Singh, Awadhesh Kumar
Summary: The cognitive radio network (CRN) is an emerging technology where communication among secondary users (SUs) takes place in an opportunistic manner. Since, a backbone eases the routing, reduces communication overhead, and efficiently handles the dynamic changes in the network. Therefore, we intend to propose a backbone formation algorithm in CRN. However, finding optimal backbone is equivalent to find minimum connected dominating set (CDS) for the given network, which is NP‐complete. Hence, the backbone construction problem can be better handled by optimization algorithms than the deterministic ones. The bio‐inspired is an interesting category of optimization algorithms. Therefore, it has been popularly used to handle various optimization problems in wireless networks. However, it has never been used for backbone construction in CRN. The ant colony optimization (ACO) is a promising bio‐inspired method because it has been effectively used to handle many problems in wireless networks, e.g. cluster head selection, leader election, routing etc. Therefore, we use ant colony system (ACS) for backbone formation in CRN. Also, the approach helps us to find optimized path between any pair of nodes to ensure efficient communication. To the best of our knowledge, it is the first bio‐inspired backbone construction algorithm in CRN. Abstract : The cognitive radio network (CRN) is an emerging technology where communication among secondary users (SUs) takes place in an opportunistic manner. We have proposed a backbone algorithm to ease routing, reduce communication overhead and efficiently handle the dynamic changes in the CRN. This is the first bio‐inspired backbone formation protocol which is more efficient and optimized compared to existing algorithms.